Microsomal triglyceride transfer protein in CaCo-2 cells: characterization and regulation. - S N Mathur; E Born; S Murthy; F J Field (Journal of Lipid Research, 1997)
As microsomal triglyceride transfer protein (MTP) is required for the assembly and secretion of apoB-containing lipoproteins by intestinal epithelial cells, the characterization and regulation of MTP in human intestinal cells, CaCo-2, was studied. CaCo-2 cells express MTP mRNA of 4.2 kb and a 97 kDa subunit of MTP protein. Similar to the expression of apoB mRNA, MTP mRNA expression was dependent upon cell differentiation and was directly related to the ability of the cells to assemble and secrete apoB-containing lipoproteins. MTP mRNA expression was highest in fully differentiated cells, with small but detectable amounts found in undifferentiated cells. Under conditions of increased apoB secretion by oleic acid, phosphatidylcholine, or lysophosphatidylcholine, MTP mass, MTP activity, and MTP gene expressions were not altered. In cells treated with calcium ionophore or phorbol 12-myristate 13-acetate, no relationship could be established between apoB secretion and MTP mRNA or activity. Similarly, in cells treated with sphingomyelinase, trifluoperazine, verapamil, okadaic acid, vanadate, or monensin, agents that decrease apoB secretion, no corresponding decrease in MTP activity or mass was observed. The results suggest that the various mediators of apoB secretion alter steps in lipoprotein assembly and secretion that are not dependent on MTP activity. CaCo-2 cells have an abundant supply of MTP for the assembly of lipoproteins when apoB secretion is stimulated by dietary lipids.